THE IMPROVEMENT OF STUDENTS LEARNING OUTCOMES IN HEAT AND ITS TRANSFER WITH THE NUMBERED HEADS TOGETHER (NHT) COOPERATIVE LEARNING MODEL IN PRIMARY SCHOOL - Engkus Suryadi (Universitas Tanjungpura, 2020)
The problem in this study was the improvement of student learning outcomes in heat and its transfer with the Numbered Heads Together (NHT) Cooperative Learning Model in V grade students at SDN 18 Sungai Ambawang. The research method used was descriptive research. The study was classroom action research with a collaborative nature with a teacher. The subjects in this study were 14 students of V grade at SDN 18 Sungai Ambawang, Sungai Ambawang District. Data collection techniques in this study were measurement techniques. The instrument used was the observation sheet. The results of this study were as follows: (1) Learning planning with NHT Cooperative Learning Model in improving student learning outcomes on the subject of heat and its transfer in V grade at SDN 18 Sungai Ambawang has been implemented well. It can be seen from the teacher's ability in designing lesson plan (RPP) in the first cycle the average was 66.9, while in the second cycle, it increased to 89.7; (2) The implementation of NHT Cooperative Learning Model in improving student learning outcomes on heat and its transfer material in V grade at SDN 18 Sungai Ambawang has been carried out well, this can be seen from the average teacher activity in the first cycle was 62.5 increases to 92.5 in cycle II (3) There was an increase in student learning outcomes, as evidenced by the increase in the average score of student learning outcomes from cycle I, namely 61.07 to 71.42 in cycle II. It has achieved the minimum completeness criteria (KKM) target of 60 and showed a significant increase.